A thin-layer amperometric sensor for hydrogen sulfide: the use of microelectrodes to achieve a membrane-independent response for Clark-type sensors. - Lawrence, N; Jiang, L; Jones, T; Compton, R (2003)
An electrochemical cell design of the Clark type including a thin layer of electrolyte in contact with a microelectrode has been successfully applied for the determination of sulfide utilizing its electrochemically initiated reaction with aqueous diethyl-p-phenylenediamine. The analytical parameters obtained were independent of the membrane used to separate the inner chamber and the outside sulfide-containing solution. The independence arises since the thickness of the diffusion layer associated with the microelectrode is small and, in contrast to the conventional macroelectrode Clark electrode, does not impinge on the membrane. This provides an improvement in gas sensor design and development as it obviates the need for membrane calibration and should simplify the application of Clark cells for variable-temperature measurements.